PRECISION MOTION SYSTEM FOR OPTO-MECHANICAL EQUIPMENT OF MICROELECTRONICS - I. V. Dainiak; S. E. Karpovich; N. I. Kekish; L. Goldyn (Наука и техника, 2015)
The paper proposes a structure of precision motion system built on the basis of a circular multi-coordinate synchronous segment motor and reconfigurable parallel kinematic mechanism. The multi-coordinate synchronous segment motor may have from two to six movable segments depending on the design, and number of the segments generally defines an internal mobility of the motor. A specific feature of the parallel kinematic mechanism consists in the possibility of its structure reconfiguration by serial connection of two neighboring rods with the help of free elements of their spherical joints into triangular circuits with one spherical hinge at the common vertex. As result of this, the controlled motion of motor movable segments is transformed into the complex spatial displacement of circular platform with number of degrees of freedom up to six inclusively.A mathematical model for solution of the kinematic problem in the investigated parallel mechanism has been offered in the paper. The model allows to calculate a position of movable segments of multi-coordinate synchronous motor depending on the desired position and orientation of the executive circular platform. The parametric definition of base point positions in the motor segments in time allows eventually to form algorithms of programmable motions.The paper substantiates ability to embed the developed motion system into projection unit of opto-mechanical equipment while preserving traditional configuration scheme. This provides the possibility of adaptive adjustment of optical elements during operation; it allows to adjust the optical elements when the geometry of projection system is changed due to deterioration. As result, main characteristics of projection system: resolution, depth of field and image contrast and distortion are maintained at the required level. The developed motion system can be used as a coordinate system of positioning, alignment and scanning in the assembly and other precision equipment.